Opportunities for intra-university collaborations in the new research environment. Issue 3 (16th April 2019) - Steel, Kathryn M.; Thompson, Helen; Wright, Wendy
ABSTRACT: New opportunities for research collaborations within universities are explored through reflection on a recent collaboration between an academic researcher, the library and the eResearch Centre at a regional Australian university. Such opportunities arise from significant changes to the research landscape, including increased emphasis on open access publication of research outputs and the growth of eResearch capabilities. The latter has resulted in increases in data size and complexity and provides opportunities for collaboration across research institutions. This article reflects on the dynamics and assesses the outcomes of a collaboration formed during an externally funded open research data project. This project and a precursor project are briefly described, together with the specific contribution of each collaborator. Collaboration dynamics and the reasons for project success are assessed, as are implications for future research practice. Outcomes from eResearch collaborations may provide broader benefits to universities, as well as rewards to academic researchers.